2022
DOI: 10.3390/en15082719
|View full text |Cite
|
Sign up to set email alerts
|

Current Trends in Waste Plastics’ Liquefaction into Fuel Fraction: A Review

Abstract: Polymers and plastics are crucial materials in many sectors of our economy, due to their numerous advantages. They also have some disadvantages, among the most important are problems with the recycling and disposal of used plastics. The recovery of waste plastics is increasing every year, but over 27% of plastics are landfilled. The rest is recycled, where, unfortunately, incineration is still the most common management method. From an economic perspective, waste management methods that lead to added-value pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 188 publications
0
14
0
Order By: Relevance
“…on the compositions of pyrolysis products, Table S8: Effects of EA,1c on the compositions of pyrolysis products, Table S9: Effects of EA,2c on the compositions of pyrolysis products, Table S10: Effects of EA,3c on the compositions of pyrolysis products. Conversion of "Wax" into "LLp" k2,P 100.00 1.00×10 5 Lechleitner et al [15] Conversion of "Wax" into "Gasp" k3,P 249.00 5.00×10 14 Lechleitner et al [15] Conversion of "SOp" into "LLp" k4,P 166.00 2.90×10 8 Schubert et al [14] Conversion of "SOp" into "Gasp" k5,P 213.00 5.42×10 6 Schubert et al [14] Conversion of "LLp" into "Gasp" k6,P 150.00 6.17×10 7 Schubert et al [14] Conversion of "Wax" into "Char" k1,C 232.67 1.07×10 Highlights  A lumped model with six components describes the pyrolysis of polypropylene.  The model consisted of ten monomolecular, irreversible, first-order reactions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…on the compositions of pyrolysis products, Table S8: Effects of EA,1c on the compositions of pyrolysis products, Table S9: Effects of EA,2c on the compositions of pyrolysis products, Table S10: Effects of EA,3c on the compositions of pyrolysis products. Conversion of "Wax" into "LLp" k2,P 100.00 1.00×10 5 Lechleitner et al [15] Conversion of "Wax" into "Gasp" k3,P 249.00 5.00×10 14 Lechleitner et al [15] Conversion of "SOp" into "LLp" k4,P 166.00 2.90×10 8 Schubert et al [14] Conversion of "SOp" into "Gasp" k5,P 213.00 5.42×10 6 Schubert et al [14] Conversion of "LLp" into "Gasp" k6,P 150.00 6.17×10 7 Schubert et al [14] Conversion of "Wax" into "Char" k1,C 232.67 1.07×10 Highlights  A lumped model with six components describes the pyrolysis of polypropylene.  The model consisted of ten monomolecular, irreversible, first-order reactions.…”
Section: Discussionmentioning
confidence: 99%
“…Pyrolysis of plastic, specifically thermoplastics, to fuel has been shown to be a method for turning plastic waste into valuable products [5], and, therefore, could be a driving force for more proper collection of plastic waste. Plastic pyrolysis offers several advantages over other methods, including no generations of dioxins and furan [6], and the economic viability of the process [7]. This liquid fuel produced from pyrolysis can be used as a substitute for liquid fuels or as raw materials in the petrochemical industry [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in diesel engine testing, liquid fuel from PET pyrolysis will be mixed with diesel fuel, with a maximum of 20% of pyrolysis liquid fuel by volume, to maintain combustion characteristics and emissions similar to diesel fuel [40] IOP Publishing doi:10.1088/1755-1315/1201/1/012011 6 Although most studies only use one type of plastic in their pyrolysis, this is difficult to apply in practical use due to the mixed nature of everyday waste. Matuszewska et al (2022) reported that pyrolysis with mixed plastic feed resulted in 75-87% yield of bio-oil, while the remaining 13-25% comprised gas and char [41]. The bio-oil yield has a higher value when compared to the yield produced from the pyrolysis of HDPE and PET.…”
Section: Pyrolysis Technology For Plastic Wastementioning
confidence: 99%
“…The causes for this outcome, amongst others, are the complexity of these methods, their lengthy reaction times, excessive energy demand, or the bad quality of the obtained products [47]. A current study on plastic waste liquefaction into fuel technologies on the worldwide market reveals that only two companies have built a full-size pyrolysis plant: Plastic Energy and Cynar Plc [41]. Plastic Energy owns two operational plants (each with a capacity of 5,000 tons of plastic waste per year) in Almeria and Sevilla, Spain, which can convert one ton of plastic waste to 850 L of TACOIL (crude oil).…”
Section: Potential Quantity Of Liquid Fuel Produced By the Pyrolysis ...mentioning
confidence: 99%
See 1 more Smart Citation